Implementation of Medan Mayor Regulation Number 27 of 2018 Concerning Drainage Management in Medan Tembung District from the Perspective of Siyasah Dusturiyah - Mhd Arkan Maulana Siregar; Zulkifli Nas (Institut Agama Islam Nahdlatul Ulama Tuban, 2026)
This study evaluates the implementation of Medan Mayor Regulation Number 27 of 2018 concerning drainage management in Medan Tembung District from the perspective of siyasah industrial and maqāṣid al-syarīʿah. A normative-empirical approach was used: primary data were obtained through interviews with officials and field observations conducted in 2025; secondary data were in the form of Perwal 27/2018, technical documents, and fiqh siyasah literature. Qualitative analysis compared norms and practices and assessed the extent to which the implementation of the Perwal met the objectives of maqāṣid, particularly ḥifẓ al-nafs (protection of life/health) and ḥifẓ al-māl (protection of property). The results showed that the implementation of the Perwal has not been optimal: maintenance is more reactive than scheduled, sediment cleaning and dredging are inconsistent, there are limitations in human resources and technical equipment, and handling is not evenly distributed throughout Medan Tembung District. This condition reflects the gap between normative provisions and field reality; from a maqāṣid perspective, the fulfilment of ḥifẓ al-nafs and ḥifẓ al-māl has not been adequately achieved. The contribution of this research is to present a study of industrial siyasah that links the norms of the Mayor's Regulation with field evidence as well as normative-fiqhiyah policy recommendations to strengthen drainage maintenance based on public welfare.